Public preferences for communicating personal genomic risk information: a focus group study. (1st September 2015) - Smit, Amelia K.; Keogh, Louise A.; Hersch, Jolyn; Newson, Ainsley J.; Butow, Phyllis; Williams, Gabrielle; Cust, Anne E.
Abstract: Background: Personalized genomic risk information has the potential to motivate behaviour change and promote population health, but the success of this will depend upon effective risk communication strategies. Objective: To determine preferences for different graphical and written risk communication formats, and the delivery of genomic risk information including the mode of communication and the role of health professionals. Design: Focus groups, transcribed and analysed thematically. Participants: Thirty‐four participants from the public. Methods: Participants were provided with, and invited to discuss, a hypothetical scenario giving an individual's personalized genomic risk of melanoma displayed in several graphical formats. Results: Participants preferred risk formats that were familiar and easy to understand, such as a 'double pie chart' and '100 person diagram' (pictograph). The 100 person diagram was considered persuasive because it humanized and personalized the risk information. People described the pie chart format as resembling bank data and food (such as cake and pizza). Participants thought that email, web‐based platforms and postal mail were viable options for communicating genomic risk information. However, they felt that it was important that a health professional (either a genetic counsellor or 'informed' general practitioner) be available for discussion at the time of receiving the risk information, to minimize potential negative emotional responses and misunderstanding. Face‐to‐face or telephone delivery was preferred for delivery of high‐risk results. Conclusions: These public preferences for communication strategies for genomic risk information will help to guide translation of genome‐based knowledge into improved population health.